FAKTOR - FAKTOR YANG MEMPENGARUHI KINERJA AUDITOR (Studi Empiris Pada KAP Di Semarang) - Nur Azizah, 12.05.52.0198; Setyowati, Widhy (Students Journal of Accounting and Banking, 2016)
This study aimed to examine the effect of the independence, professionalism, professional ethics, leadership style and organizational culture which directly affects the performance of the auditor in public accounting firm in the city of Semarang. The population in this study is the auditor who worked on a public accounting firm in the city of Semarang. Sampling was done by using a convenience sampling method and the total sample of 53 respondents. Primary data collection method used is the questionnaire. Data were analyzed using multiple linear regression model. The results showed that the independence and leadership style is not significant positive effect on the performance of auditors. While professionalism, professional ethics and organizational culture have a significant positive effect on the performance of auditors. Keywords: Independence, Professionalism, Professional Ethics, Leadership Style, Organizational Culture, Performance Auditor